An automatic method to track red blood cells in microchannels - Pinho, Diana (2014)
Image analysis is extremely important to obtain crucial information about the blood phenomena in micro-circulation. The current study proposes an automatic method for segmentation and tracking red blood cells (RBCs) flowing through a 100 μm Glass capillary. The original images were obtained by means of a confocal system and then processed in Matlab using the Image Processing Toolbox. The automatic measurements ob-tained with the proposed automatic method are compared with a manual tracking method using a plugin from ImageJ.